Strategi Pemasaran dalam Meningkatkan Usaha UMKM Teh Poci Cahya di Cibitung (IJM: Journal of Multidisiplinary, 2024)
Tea is a beverage that is highly suitable for enjoying in tropical environments like Indonesia, especially during hot weather. This drink not only refreshes but can also be served in various ways, both hot and cold, according to consumer preferences. Besides its delightful taste, tea is rich in nutrients beneficial for health. The diverse flavors offered by Teh Poci Ibu Cahya are well-known among tea enthusiasts. This product is renowned not only for its delicious taste but also for its affordability, attractive packaging, and wide availability in various retail outlets. In order to boost sales in the Cibitung region, the company plans to implement different marketing strategies to attract more consumers and increase revenue. This research aims to evaluate the strengths and weaknesses of the marketing approach for Teh Poci Ibu Cahya in that area, thus providing appropriate recommendations for enhancing and boosting sales of the product.